Causas de retiro de dispositivo intrauterino de cobre e implante subdérmico etonogestrel en usuarias del Centro Materno Infantil Julia Esther González Delgado - Cango Jiménez, Adriana Stefanía (2020)
Long-term reversible contraceptive methods such as the copper intrauterine device (copper IUD) and subdermal implant (etonogestrel) have great acceptability by users who want family planning, however, the emergence of various adverse effects that can be intolerable force them to abandon them. Due to the importance of reducing the morbidity and mortality of women with their use and knowing the impact that they can cause on their health, I consider it necessary to know the main causes of early withdrawal of these methods, to determine which of these methods are more frequently withdrawn and set the time of use before removing them. This study is descriptive retrospective, whose information was collected from medical records of users who attended the Maternal and Child Center "Julia Esther González Delgado" in the period January 2013 - December 2017 to withdraw these contraceptive methods. The results determine that: the main causes of removal of such implant and of the copper IUD are menstrual abnormalities 31.43% (mainly metrorrhagia) and 50% (mainly hypermenorrhea), respectively, 51.94% had the implant removed and 48.06% the copper IUD, the time of use greater than 12 months with the implant was 67.16% and the copper IUD 48.39%. In conclusion, the main causes of removal of the two methods are associated with menstrual disturbances, the method that was mostly removed was the subdermal implant the subdermal and in both contraceptive methods the highest frequency of removal was after 12 months of use. Key words: contraceptive methods, adverse effects, metrorrhagia, hypermenorrhea